2022
DOI: 10.1523/jneurosci.0148-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Neural Contributions to Reduced Fluid Intelligence across the Adult Lifespan

Abstract: Fluid intelligence, the ability to solve novel, complex problems, declines steeply during healthy human aging. Using fMRI, fluid intelligence has been repeatedly associated with activation of a frontoparietal brain network, and impairment following focal damage to these regions suggests that fluid intelligence depends on their integrity. It is therefore possible that age-related functional differences in frontoparietal activity contribute to the reduction in fluid intelligence. This paper reports on analysis o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 123 publications
0
2
0
Order By: Relevance
“…For example, these findings could be connected to the ERP research that has interpreted the domain-general P600 component (e.g., Osterhout & Holcomb, 1992;Patel, 2003;Núñez-Peña & Honrubia-Serrano, 2004;Cohn et al, 2012) as indexing error correction (Ryskin, Stearns et al, 2021). Our findings also make predictions about the processing of syntactically corrupt inputs in children and older adults (given that the MD network is slow to develop (Fiske & Holmboe, 2019;Schettini et al, 2023) and shows clear age-related decline (Reuter-Lorenz et al, 2000;Mitchell et al, 2023;Wu & Hoffman, 2023)). If the MD network cannot effectively support syntactic reconstruction in these populations, we should observe larger effects of syntactic degradation on the language network's responses, and greater reliance on semantic plausibility in interpreting corrupt inputs (e.g., Beese et al, 2019).…”
Section: Limitations Future Directions and Open Questionssupporting
confidence: 67%
“…For example, these findings could be connected to the ERP research that has interpreted the domain-general P600 component (e.g., Osterhout & Holcomb, 1992;Patel, 2003;Núñez-Peña & Honrubia-Serrano, 2004;Cohn et al, 2012) as indexing error correction (Ryskin, Stearns et al, 2021). Our findings also make predictions about the processing of syntactically corrupt inputs in children and older adults (given that the MD network is slow to develop (Fiske & Holmboe, 2019;Schettini et al, 2023) and shows clear age-related decline (Reuter-Lorenz et al, 2000;Mitchell et al, 2023;Wu & Hoffman, 2023)). If the MD network cannot effectively support syntactic reconstruction in these populations, we should observe larger effects of syntactic degradation on the language network's responses, and greater reliance on semantic plausibility in interpreting corrupt inputs (e.g., Beese et al, 2019).…”
Section: Limitations Future Directions and Open Questionssupporting
confidence: 67%
“…These findings can also be contextualized with respect to past research looking at the functional neural correlates of fluid intelligence. Across a range of studies fluid intelligence has been associated with regions in the frontopartietal network (Barbey et al, 2014; Gläscher et al, 2010; Mitchell et al, 2023; Momi et al, 2020; Samu et al, 2017; Smith et al, 2022; Woolgar et al, 2010). We found that YA relied on the mPFC and IPL regions of this network, in line with past research.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies focused exclusively on how dedifferentiation mediates poorer performances in fluid intelligence (Mitchell et al, 2023) and long-term memory (Koen et al, 2020), this study aimed to model the neural mechanisms that bridge dedifferentiation and compensation (section 3.3), and how the changes in this dedifferentiation-compensation dynamic relate to the age-related variability in language abilities discussed previously. Overall, we suggest that dedifferentiation-compensation follows the principle of the economy of brain network organization (Bullmore & Sporns, 2012).…”
Section: Dedifferentiation-compensation Mechanismsmentioning
confidence: 99%